2018
DOI: 10.1016/j.cmpb.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for healthcare applications based on physiological signals: A review

Abstract: This review paper depicts the application of various deep learning algorithms used till recently, but in future it will be used for more healthcare areas to improve the quality of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
457
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 833 publications
(462 citation statements)
references
References 101 publications
(68 reference statements)
1
457
0
4
Order By: Relevance
“…Most previous EMG studies using deep learning, however, have approached the model selection and parameter optimization processes without statistical methods (i.e., a single run trial instead of cross validation [116]). Caution should therefore be taken when comparing the classification performances of proposed deep learning algorithms with more shallow learning conventional algorithms (e.g., LDA and SVM) which require a smaller training dataset and whose presentation has more commonly employed cross validation.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous EMG studies using deep learning, however, have approached the model selection and parameter optimization processes without statistical methods (i.e., a single run trial instead of cross validation [116]). Caution should therefore be taken when comparing the classification performances of proposed deep learning algorithms with more shallow learning conventional algorithms (e.g., LDA and SVM) which require a smaller training dataset and whose presentation has more commonly employed cross validation.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of data was conducted in a simple way. Some of the methods used for synthesis were in accordance with other similar studies [63][64][65]. According to the gathered data, the most widely used deep learning method is convolutional neural networks (CNNs).…”
Section: Discussing the Resultsmentioning
confidence: 73%
“…These applications were not so represented in the past. Traditional approaches to various similarity measures are ineffective when compared to deep learning [63]. Based on these findings, it can be suggested that deep learning and deep neural networks will prevail, and that they will find many other uses in the near future.…”
Section: Research Questionsmentioning
confidence: 99%
“…field of image processing [3][4][5][6][7]. Similar performances have been achieved in the field of 25 speech recognition [8,9] and natural language processing [10,11]. 26 A steadily growing amount of work has been exploring the application of deep 27 learning approaches on physiological signals.…”
mentioning
confidence: 84%
“…Most of the reported 49 approaches consist of first transforming the processed EMG signal into a two 50 dimensional (time-frequency) visual representation (such as a spectrogram or a 51 scalogram) and subsequently using a deep CNN architecture to proceed with the 52 classification. A similar procedure has been used in [24] for the analysis of deep learning approaches applied to physiological signals can be found in [25] and [26]. 56 The current work focuses on the application of deep learning approaches for 57 nociceptive pain recognition based on physiological signals (EMG, ECG and 58 April 23, 2019 2/16 electrodermal activity (EDA)).…”
mentioning
confidence: 99%